2019
DOI: 10.1177/1938640019846970
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Fusion Preparation: What Are We Really Doing? A Cadaver Study

Abstract: Introduction. The open, lateral sinus tarsi approach is the most commonly used technique for subtalar arthrodesis. In this cadaver study, we measured the maximum joint surface area that could be denuded of cartilage and subchondral bone through this approach. Methods. Nine fresh frozen above-knee specimens were used. The subtalar joint was accessed through a lateral incision from the fibular malleolus distally over the sinus tarsi area to the level of the calcaneocuboid joint. Cartilage was removed from the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It remains unclear how much cartilage of a joint has to be removed to obtain a mechanically stable arthrodesis. A cadaver study of Abyar et al 1 demonstrated that the percentage of total unprepared articular surface area was mean 8.7% when performing subtalar arthrodesis via the most frequently used open lateral sinus tarsi approach. Klassen et al 9 reported a nonunion rate of 8.9% after subtalar joint arthrodesis in a retrospective analysis of 157 cases.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear how much cartilage of a joint has to be removed to obtain a mechanically stable arthrodesis. A cadaver study of Abyar et al 1 demonstrated that the percentage of total unprepared articular surface area was mean 8.7% when performing subtalar arthrodesis via the most frequently used open lateral sinus tarsi approach. Klassen et al 9 reported a nonunion rate of 8.9% after subtalar joint arthrodesis in a retrospective analysis of 157 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Anticipated mean and standard deviation was estimated from prior joint preparation studies. 1,8,9 Alpha was set at 0.05 and power at 80%. The joints of interest for this study included the tibiotalar joint, posterior facet of the talocalcaneal joint, TN joint, CC joint, NC joint, TMT joints of rays 1-3, hallux MTP joint, and hallux IP joint.…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution pictorial images of both joint surfaces were obtained. Estimated fusion contact area was assessed and outlined, and the total fusion contact surface area and the amount of unprepared cartilage on the proximal phalanx and distal metatarsal head were measured using ImageJ software (Figure 2 ) [ 12 - 14 ]. These measurements were used to calculate the percentages of prepared and unprepared cartilage of each articular surface for each specimen.…”
Section: Methodsmentioning
confidence: 99%